Correction: Application of QM/MM and QM methods to investigate histone deacetylase 8 - Duangkamol Gleeson; M. Paul Gleeson (My University, 2015)
Correction for ‘Application of QM/MM and QM methods to investigate histone deacetylase 8’ by Duangkamol Gleeson et al., Med. Chem. Commun., 2015, 6, 477–485.
Keywords: Histone Deacetylase Inhibitors Research